The importance of consumer taste in trade - Bee Yan Aw; Yi Lee; Hylke Vandenbussche (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper documents the importance of consumer taste in trade flows using Belgian firm-product customs data by destination. We identify consumer taste through the use of a control function approach and estimate it jointly with other demand parameters using a very flexible demand specification. Consumer taste is identified for every trade ow. The results show that taste decreases in distance but this relationship is not monotonic. The contribution of consumer taste to actual export revenue ranges between 1-31% depending on the product category in the food industry. Overall, the demand shifters, taste and product quality explain twice as much of the variation in export revenues than cost.
Keywords: F12; F14; 330; tastes; quality; productivity; exports; firm-product